Board characteristics and corruption in Malaysian GLCs / Azizah Abdullah … [et al.] - Md Daud, Seri Ayu Masuri; Saad, Shukriah; Abdul Aziz, Rozainun; Najid, Nurul Afzan (Faculty of Accountancy, 2019)
This study examines whether there are any systematic differences between the boards of directors’ characteristics of alleged corrupt government-linked companies (GLCs) in Malaysia and their matched perceived clean GLCs. Drawing on extant literature of board governance and corruption, we argue that having more politically connected directors or more ex-senior government officers in the board, and CEO duality increase the likelihood of corruption in a company. In contrast, having more industry, accounting, or legal experts on the board will likely enhance the board efficacy and hence curb corruption. The result of independent samples t-test suggests that only the percentage of politically connected directors, ex-senior government officers, and accounting experts on the board of the perceived corrupt GLCs are significantly different from the matched- clean GLCs. Using this latter finding, we propose that the probability of corruption in a GLC is a function of the three significantly different board characteristics, ceteris paribus. Particularly, a mathematical equation is formulated to predict the probability of corruption using the p-value of each of the three board characteristics corresponding to the given test statistic as weightage of each variable. Finally, a corruption likelihood indicator is developed based on the mean percentage of politically connected directors, ex-senior government officers, and accounting experts on the board for perceived corrupt (red zone i.e. highly likely corrupt) and clean (green zone i.e. highly likely clean) GLCs. This indicator is expected to be a useful tool to help GLCs assess their board governance strength and hence exposure to corruption.